Enhancing Teacher Professionalism Culture through Principal Leadership Strategies - Elva Choirum Milati; Khoirun Nisa’; Adi Wibowo (Al-Qalam Institue, 2026)
The culture of teacher professionalism is a crucial factor in improving educational quality, as it reflects teachers’ commitment, responsibility, and continuous professional development. This study aims to examine the strategies employed by school principals in fostering a culture of professionalism among teachers. A qualitative research approach with a descriptive design was used to explore leadership practices and their influence on professional culture. Data were collected through observations of leadership practices and professional activities, in-depth interviews with the principal and teachers, and documentation analysis of school programs and organizational records. The findings reveal that principals enhance teacher professionalism through structured coaching, role modeling, supervision, professional development programs, and the cultivation of collaborative work environments. These strategies contribute to increased teacher discipline, professional responsibility, and engagement in continuous improvement. The study implies that effective principal leadership plays a central role in shaping a sustainable culture of teacher professionalism. Therefore, school leaders are encouraged to adopt strategic, participatory, and consistent leadership practices to strengthen professional culture and support long-term educational quality improvement.